(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article substantiates the fact that fundamentally new visions on the use of the Armed Forces of Ukraine are being developed during the full-scale war of Ukraine against Russia, including new concepts of war and strategies for using the army during wartime, rearmament of troops according to NATO standards, creation of new structures, an improvement of forms, types, and methods of pedagogical activity of military personnel, in particular for military officers. The maintenance and even increase of requirements for the quality of professional training for military personnel during martial law requires serious changes in the pedagogical training of military officers. The article aims to analyze the phenomenon of the pedagogical culture of future military officers, as well as to reveal its basic and functional components. The paper also focuses on the effective mechanisms of forming such culture within the framework of professional and pedagogical training in higher military educational institutions. Research goals: to analyze scientific research on the chosen issue; to consider the structural basic and functional components of the pedagogical culture of future military officers; to explore professional and pedagogical training in higher military educational institutions as an environment for the formation of the pedagogical culture of future military officers. The author employed a set of interrelated research methods to accomplish the assigned goals. These methods include logical, structural, and structural-systemic analysis of scientific research on the identified problem, synthesis, and generalization. Overall, pedagogical culture reflects a set of certain pedagogical abilities, skills, interests, value orientations, personal qualities, and the desire for continuous development and improvement. The formation of the pedagogical culture of future military officers facilitates the development of their own professional and pedagogical stance as part of implementing various types of military and pedagogical activities by officers. It has been found that the formation and development of military officer's pedagogical culture is a complex process that continues throughout their professional life. Basic principles of pedagogical culture are laid in pedagogical training in military educational institutions.